Evaluation of Physical Education Learning Program During the Covid 19 Pandemic at the Secondary Education Level - Suastika Nurfiati; Liska Sukiyandari (Universitas Negeri Semarang, 2022)
This research is a qualitative research that aims to identify and analyze physical education learning programs during the Covid-19 pandemic in the 2019-2020 school year. The research technique used is the interview method with data collection using interview tests, observation and documentation. The subjects in this study were MTsN 2 and SMPN 11. The results of this study are: (1). The context of the physical education learning program during the Covid-19 pandemic uses the 2013 curriculum by making lesson plans in accordance with the pandemic conditions, by adjusting indicators and learning objectives (2). Physical education learning program inputs are very good and appropriate, as evidenced by the latest education is S1, the teacher has more than 10 years of teaching experience and has participated in teacher performance training programs and teaching development training (3). Physical education learning program process is carried out online for MTsN 2 providing LMS and supporting applications in the network such as zoom, WhatsApp Group, google meet and for SMPN 11 schools using WhatsApp Group to send learning outcomes.